Mulheres, arte e poder: uma narrativa de contrapoder? - Ana Gabriela Macedo (Estudos de Literatura Brasileira Contemporânea)
My aim in this paper is to build on a fundamental essay by Linda Nochlin preci- sely titled “Women, Art and Power” (1988), where the author convincingly inves- tigates this triad while, in her own words, she “disentangles various discourses about power related to gender difference existing simultaneously with – as much surface as substractum – the master discourse of the iconography or narrative”. I propose to extend Nochlin’s analysis somehow further and, without twisting her premises, to introduce a shift of focus in this debate, from the analysis of the repre- sentation of women by male artists, to the role of the woman artist in contempo- rary art scene, i.e., from women as objects of representation, to women as agents and subjects of the representation. This situation, which has indeed gained wider significance since the late 80s, I suggest (through the viewing of some examples), can be read within the context of the production of women’s narratives of empo- werment or, alternatively, as creating challenging narratives of counter-power.